Role of BATAN in Establishing Nuclear Oncology in Indonesia - Hastowo, Hudi (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45478916/Role-of-BATAN-in-Establishing-Nuclear-Oncology-in-Indonesia